Rare bird documentation form for Peregrine Falcon near Cedar Rapids, 1979 - Newlon, Michael C.et al (1979)
Rare bird documentation form for a Peregrine Falcon near Cedar Rapids in Linn County, IA on September 30, 1979. Epson - sheet feed